Molecularly imprinted polymer (MIP) based electrochemical sensors and their recent advances in health applications - Wang, Lue; Pagett, Matthew; Zhang, Wei (Sensors and actuators reports, 2023)
•Molecularly imprinted polymer (MIP)-based electrochemical sensors have been received growing attention over past decades owing to its robust nature, simple electrochemical control for template removal and cavity regeneration, and go-as-you-please cavity designs into various geometries specific to target analytes.•Some electrodes (e.g., SPE) used in MIP-based electrochemical sensors have great potential of mass production but lack a detailed manufacture workflow specific to the massive production in industrial lines and batch-to-batch quality assessment.•At present, MIP-based electrochemical sensors with limited autonomous capability (i.e. the self-controlled ‘sample loading – sensing – electrode surface washing’) still account for a large proportion.•Laboratory-grade sensing devices often lack adequate exploration on desirable portability according to recent advances on electrochemical MIP sensors.•Future investigation should focus on the development of MIP-based sensors suitable for being tested in undiluted conditions. Molecularly imprinted polymer (MIP)-based electrochemical sensors have received growing attention over past decades owing to its robust nature, simple electrochemical control for template removal and cavity regeneration, and go-as-you-please cavity designs into various geometries specific to target analytes. The strength of MIP scheme, in combination with the advantages of electrochemical sensing techniques such as operation simplicity, rapid response, and high sensitivity, provide a synergistic effort to form a highly effective sensing platform suitable for an extremely wide range of interest. In this Review, the introduction of MIP and the comparison between electrochemical sensing methods and other detection strategies are briefly discussed. Then, a broad range of analytes determined using MIP-based electrochemical sensors are listed and critically reviewed, mainly focusing on the applied electrochemical technique, presented linear range along with limit of detection (LOD), biological fluid used in real testing, and pretreatment for real sample. Other sensor performances like selectivity towards analyte, signal repeatability, sensor-to-sensor reproducibility, and stability, are carefully compared with other reported papers. MIP sensors fabricated via the nanoMIP technology, and the ones integrated with portable analyzers, are given in more details as good results are always observed in such instances. Finally, a conclusion regarding recent advances on MIP-based electrochemical sensors is presented, followed by current issues and future development depicted at the last section of the Review. [Display omitted]